1999
DOI: 10.1080/00288233.1999.9513349
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of endophyte‐infected perennial ryegrass extracts on white clover seedlings

Abstract: Two glasshouse experiments were conducted to evaluate possible allelopathic effects of perennial ryegrass/endophyte (Lolium perennel Neotyphodium lolii) associations on white clover (Trifolium repens). The influence of betweenspecies competition, environmental stress, and soil fauna was eliminated by the use of a sterile sand nutrient culture technique to sustain potted clover seedlings, to which aqueous extracts from moisturestressed perennial ryegrass pseudostem were applied. In Experiment 1, extracts from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…While our design did not allow specific mechanisms to be recognized, other studies have suggested that allelopathic effects could be involved in the observed dominance of some grassendophyte associations (Orr et al 2005;Antunes et al 2008). Toxic compounds produced by symbiosis might persist in the host's dead remains and be leachated to the soil (Sutherland et al 1999;Fletcher 2005;Antunes et al 2008). This may explain why the litter of infected plants decomposed more slowly than that of endophyte-free plants (Omacini et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our design did not allow specific mechanisms to be recognized, other studies have suggested that allelopathic effects could be involved in the observed dominance of some grassendophyte associations (Orr et al 2005;Antunes et al 2008). Toxic compounds produced by symbiosis might persist in the host's dead remains and be leachated to the soil (Sutherland et al 1999;Fletcher 2005;Antunes et al 2008). This may explain why the litter of infected plants decomposed more slowly than that of endophyte-free plants (Omacini et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2008). Toxic compounds produced by symbiosis might persist in the host’s dead remains and be leachated to the soil (Sutherland et al. 1999; Fletcher 2005; Antunes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the specific effect of CTE+ tall fescue on clover when grown together, though a recent greenhouse study found no effect (Dirihan et al 2014). In contrast, three genotypic strains of Epichloë lolii (previously Neotyphodium lolii Leuchtmann et al 2014), another asexual fungal endophyte species, infecting perennial ryegrass decreased growth of white clover when grown in mixture, but differences between endophyte strains were not attributed to strain-specific alkaloid profiles (Sutherland et al 1999). Root and leaf extracts of red fescue infected with Epichloë festucae reduced seed germination of both red and white clover (Vázquez-de-Aldana et al 2011), and E. festucae-infected red fescue has also been shown to inhibit red clover biomass production and reduce growth of other legumes when grown in mixture (Vázquez-de-Aldana et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, in tall fescue, Peters and Mohammed Zam (1981) found reduced germination and root growth of red clover and birdsfoot trefoil when subjected to tall fescue extracts of unknown endophyte status, and Springer (1996) later found that extracts from both E-and CTE+ tall fescue reduced red clover germination and root growth. Inhibition of forage legumes when grown in mixture with CTE+ fescue may be due to allelopathic effects (Springer 1996;Sutherland et al 1999;Vázquez-deAldana et al 2013;Vázquez-de-Aldana et al 2011), or to other competitive effects such as increased soil moisture stress or decreased light interception (Staley and Belesky 2004). Yet, because formation of bacterial symbiosis for BNF and fixation activity is linked to legume growth and development (e.g., Delves et al 1986;Robson et al 1981), we must consider whether endophyte-infected tall fescue influences these characteristics that may contribute to inhibition of legumes.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the fungal endophytes Neotyphodium coenophialum and Neotyphodium lolii are associated with tall fescue (Lolium arundinaceum) and ryegrass (Lolium perennel), respectively. These endophytes increase allelopathic and competitive ability of the host plants, reducing the diversity of the surrounding plant community (Clay and Holah 1999;Sutherland et al 1999). These interactions have been shown to affect ecosystem processes, for example, soil respiration (Madritch and Hunter 2003) and decomposition (Hector et al 2000;Knops et al 2001;Gartner and Cardon 2004).…”
Section: Introductionmentioning
confidence: 99%